2016
DOI: 10.1177/0734016816634787
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Reporting (MR) in Higher Education

Abstract: Mandatory reporting (MR) policies concerning sexual assault victimization now extend to institutions of higher education. The laws are new and thus controversial since relatively little investigation into their impact has occurred. Additionally, since the laws require disclosure to police, at times, even in instances where victims object, opponents have expressed concerns about potential unintended effects, such as diminished victim autonomy. Perhaps, though, the most glaring question involves how college stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The small body of existing research has primarily focused on students' knowledge and perceptions of mandatory reporting in general, not among survivors. For instance, a study by Mancini et al (2016) found that students held mixed feelings about the efficacy of mandatory reporting, with some imagining positive outcomes (e.g., survivors receive services) and others imagining negative outcomes (e.g., survivors are stripped of autonomy). A recent doctoral dissertation (Amin, 2019) found that while many students favored mandatory reporting policies, other students indicated that mandatory reporting would hinder reporting.…”
Section: The Effects and Effectiveness Of Mandatory Reportingmentioning
confidence: 99%
“…The small body of existing research has primarily focused on students' knowledge and perceptions of mandatory reporting in general, not among survivors. For instance, a study by Mancini et al (2016) found that students held mixed feelings about the efficacy of mandatory reporting, with some imagining positive outcomes (e.g., survivors receive services) and others imagining negative outcomes (e.g., survivors are stripped of autonomy). A recent doctoral dissertation (Amin, 2019) found that while many students favored mandatory reporting policies, other students indicated that mandatory reporting would hinder reporting.…”
Section: The Effects and Effectiveness Of Mandatory Reportingmentioning
confidence: 99%
“…While there exists literature on barriers to sexual assault disclosure as well as on students' perceptions of sexual assault on campus, research on students' perceptions, understandings, and knowledge of campus sexual assault policies and/or services (Garcia et al, 2012;Mancini et al, 2016;Nasta et al, 2005;Streng & Kamimura, 2017), particularly as it relates to sexual violence on Canadian campuses, is limited (Council of Ontario Universities, 2020; Quinlan et al, 2016). Students' opinions of campus adjudication of sexual assault, and students' likelihood of reporting sexual assault to campus authorities, also remains largely unexplored (Amar et al, 2014;Orchowski et al, 2009;Taylor & Gassner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Title IX regulations in higher education provide another example of well-meaning and important policy that may encourage (un)victimization of Black women and girls. Specifically, Title IX provisions for mandated reporting of sexual violence may take agency away from victims and place it in the hands of authorities and institutional investigative offices, who, in compliance with the law, may inadvertently exacerbate problems for victims/survivors (Mancini et al, 2016). The result may be the perpetuation of the (un)victim cycle, as the interests of victims can conflict with institutional priorities.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 99%